Taxus wallichiana var. chinensis (Pilg.) Florin Aqueous Extract Suppresses the Proliferation and Metastasis in Lung Carcinoma via JAK/STAT3 Signaling Pathway - Sun, Leitao; Ding, Shuning; Luo, Qi; Wang, Peipei; Yang, Xiao; Wu, Linqin; Chen, Yangfan; Zheng, Xueer; Zhang, Hang; Yuan, Li; Ruan, Shanming; Xie, Changsheng (Frontiers in Pharmacology, 2021)
As one of the most common neoplasms globally, lung cancer (LC) is the leading cause of cancer-related mortality. Recurrence and metastasis negatively influencing therapeutic efficacy and overall survival demand new strategies in LC treatment. The advantages of TCM are increasingly highlighted. In this study, we obtained the major chemical components and their ratios in the aqueous extract of Taxus wallichiana var. chinensis (Pilg.) Florin (AETW) by UPLC-Q/TOF-MS/MS detection. CCK8 assay revealed that AETW could selectively inhibit the growth of A549 and HCC827 cells in a dose-dependent manner with little effect on normal human lung cells. Moreover, both in vitro and in vivo experiments showed that AETW was able to suppress the capacities of cell migration and invasion and downregulate the EMT and the JAK/STAT3 signaling pathway. To further probe into the molecular mechanism, overexpression of STAT3 was performed into LC cells with AETW treatment, which counteracted the inhibitory effect on malignant behaviors of A549 and HCC827 cells with the decline in the expressions of p-JAK and p-STAT3. Taken together, we propose that AETW may inhibit the proliferation and metastasis by inactivating JAK/STAT3 axis.